Radial Variations in Surface Characteristics of Pine Wood (Pinus merkusii) Modified with Glycerin–Citric Acid - Achmat Syafi'i; Mohammad Rafli Ariyansyah; Dhiyar Luthfan Hamidi; Sartika Sartika; Alia Pratiwi; Ahmad Rabbani Abdussalam; Irsan Alipraja; Wayan Darmawan; Philippe Geradin (Institut Pertanian Bogor, 2026)
Pine wood (Pinus merkusii) is a native Indonesian softwood species with high commercial value but low natural durability (class IV), limiting its use in outdoor applications. This study modified the pine wood using a 20% glycerin–citric acid solution (1:2 ratio) through impregnation with 7 bar pressure for 48 hours, followed by heat treatment at 150°C for 6 hours, to evaluate surface characteristics in radial variations (from pith to bark). Retention (57.93–85.59 kg/m³) and weight percent gain (WPG, 4.02–7.20%) decreased from pith to bark, corresponding to lower wood density near the pith (0.55 g/cm³) compared to near the bark (0.67 g/cm³). Surface roughness (Ra) varied slightly from fit to bark, however its Ra increased after modification. Surface free energy (SFE) increased significantly from 16.87 near the pith to – 27.35 mJ/m² near the bark. After modification the SFE values varied between 37.16–44.46 mJ/m² from fit to bark. Wettability (K-value) was lower near the pith (0.002) than near the bark (0.007). Glycerin–citric acid modified pine exhibited also a lower wettability values compared to the untreated wood. The surface characteristics of the modified pine wood from fit to bark indicate that its surfaces should be coated by proper varnishes or paints for further development.Keywords: citric acid, glycerin, modification, radial variation, surface characteristics